Análisis del impacto de los sistemas de riego por aspersión y microaspersión en el cultivo de cacao en la región costa - Jacome Pacheco, Erick Rafael (2025)
The research analysis entitled “Analysis of the impact of sprinkler and micro-sprinkler irrigation systems on cocoa cultivation in the coastal region”, carried out in the Canton Babahoyo in the fields of the Faculty of Agricultural Sciences, aims to evaluate how different irrigation systems affect cocoa cultivation. The methodology used was exploratory and bibliographic, which allowed for an in-depth view of the irrigation technologies used in cocoa cultivation in the coastal region. In addition, the research focused on the analysis of sprinkler and micro-sprinkler irrigation systems applied to already established crops, which provided practical and real data for the study. The comparison between the irrigation systems was fundamental in determining how each one influences the behavior and productivity of the crops. The treatments evaluated —sprinkler irrigation and micro-sprinkler irrigation— were measured by means of several variables: field capacity, wilting point, root depth and a benefit-cost analysis. These variables are crucial for evaluating water yield, crop health and the economic efficiency of the irrigation systems used. The results obtained showed significant differences between the two irrigation systems. This difference suggests that each system has a different impact on cocoa cultivation, whether in terms of the amount of water absorbed by the soil, root development or the cost-benefit ratio. It is likely that micro-sprinkler systems, which offer a more controlled and precise distribution of water, have shown advantages in terms of water efficiency and possibly in root growth, which would be reflected in higher crop productivity.